Exploring a novel treatment method to enhance polar phases in electrospun PVDF nanofibers - Ding, Guoqiang (2009)
Poly (vinylidene fluoride) (PVDF) has drawn much attention due to the attractive properties such as piezo-, pyro-, and ferroelectricity, which are rarely exhibited in other polymers. The β phase has the largest spontaneous polarization (p) per unit cell of all polar phases and thus exhibits the highest piezo-, pyro and ferroelectric activities. This project aims to enhance β phase of PVDF through electrospinning and novel treatments.